(untitled) (Journal of the College of Basic Education, 2023)
A Simple, rapid and sensitive spectrophotometric method is described for quantitative determination of ciprofloxacin. The method is based on the reaction of this drug as an n-electron donor with Methylene blue as π-acceptors to produce charge transfer complex . The complex was prepared in KCl– HCl buffer of pH 2 (method A) and in NaOAc – AcOH buffer of pH 5.2 (method B) to give highly coloured complex. The coloured product is quantitated Spectrophotometrically at 665 nm. Optimization of the different experimental conditions is described.The absorbance was found to increase linearly with increase in concentration of Ciprofloxacin which was corroborated by the calculated correlation coefficient values ( 1, 0.999). Beer,s law is obeyed in the concentration ranges 2 – 10 µg /ml of drug for Methylene blue . Various analytical parameters have been evaluated and the validated by statistical data .The proposed method is suitable for quantitative determination of ciprofloxacin in Pharmaceutical Preparations .